2019
DOI: 10.3389/fpsyg.2019.01366
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perfectionism and Controlling Conditions in Norwegian Elite Junior Performers’ Motivational Processes

Abstract: Conceptualized within the framework of self-determination theory, the aim of the current study was to investigate the relation between perfectionistic concerns and (a) controlled (non-self-determined) motivation and (b) performance anxiety through basic psychological need frustration (frustration of competence, autonomy, and realtedness), and if these relations would be moderated by controlling teaching/coaching conditions. We used a cross-sectional moderated mediation design and purposefully selected Norwegia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 61 publications
4
36
0
Order By: Relevance
“…In turn, these feelings of imperfection might influence interpersonal relations by a decrease in social status and, subsequently, frustrate the need for relatedness . In addition, as EC are linked to controlled, rigid, and neurotic behavioral regulations, EC might additionally nurture autonomy and relatedness frustration . Lastly, the lack of adaptive coping strategies to encounter stress and adversity, which have been found associated with EC might also contribute to escalation in each basic need frustration over time .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In turn, these feelings of imperfection might influence interpersonal relations by a decrease in social status and, subsequently, frustrate the need for relatedness . In addition, as EC are linked to controlled, rigid, and neurotic behavioral regulations, EC might additionally nurture autonomy and relatedness frustration . Lastly, the lack of adaptive coping strategies to encounter stress and adversity, which have been found associated with EC might also contribute to escalation in each basic need frustration over time .…”
Section: Discussionmentioning
confidence: 99%
“…13,29,42 Additionally, the vulnerability associated with a mixed perfectionism profile 58,66 is likely to be triggered within performance-oriented TDEs (ie, high expectations, competitive, and external feedback). 12,67,68 Furthermore, when experiencing basic need frustration, a heightened need to be resilient in order to encounter the maladaptive situation appears. As a paradox, research based on the SDT framework has highlighted that when less self-determined, the ability to negotiate stress and adversity to engage in resilience and restoration processes are hampered.…”
Section: Frustration Competence Frustration Autonomy Frustration Relamentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, in the field of sports, the relationship between perfectionism and self-determined motivation was also investigated. Specifically, previous studies revealed that perfectionistic strivings had a positive relationship with autonomous motivation [18,21], whereas perfectionistic concerns had a positive relationship with controlled motivation [18,21,22]. Therefore, based on the relationships among perfectionism, selfdetermined motivation and attitudes toward doping, it is possible that autonomous and controlled motivation may play a mediating role between perfectionism and athletes' attitudes toward doping.…”
Section: Introductionmentioning
confidence: 97%